Effects of Saccharomyces boulardii cell wall polysaccharide supplementation on growth performance, serum immunity, and fecal microorganisms in newborn calves - Yin, Haina; Mo, Xucheng; Zeng, Wenshuai; Zhu, Wenshu; Liu, Mengjian (Frontiers in Veterinary Science, 2025)
BackgroundXinjiang is characterized by extremely cold weather and significant seasonal temperature variations, and these harsh climatic conditions have led to a high incidence of diarrhea and increased mortality rates among newborn calves, resulting in substantial economic losses for the local cattle industry. Saccharomyces boulardii cell wall polysaccharide (SBWP) is a natural prebiotic that has emerged as a promising alternative to conventional antibiotics for the mitigation of systemic inflammation, diarrhea, and mortality in livestock production. Therefore, this study aimed to investigate the effects of SBWP supplementation on growth performance, diarrhea frequency, serum immunity, and intestinal microbiota in newborn calves.MethodsIn this study, a one-way experimental design was employed. A total of 45 newborn calves (Simmental♂ × Yili brown cattle♀, male, average body weight (BW) 35.58 ± 5.79 kg) were randomly allocated into five experimental groups. Each group consisted of three pens, with three calves per pen, and this allocation was carried out based on the percentage of SBWP used as a feed supplement. The diet for the five groups were as follows: group I received milk + basal diet without additives, group II received milk + basal diet + 0.005% gentamicin, group III received milk + basal diet + 250 mg/day/calf SBWP, group IV received milk + basal diet + 500 mg/day/calf SBWP, and group V received milk + basal diet + 1,000 mg/day/calf SBWP. Daily feed consumption was recorded, and BW was measured on days 1, 14, and 28 to calculate average daily gain (ADG), average daily feed intake, and feed-to-gain (F/G) ratio. Fecal samples were collected on days 1, 7, 14, 21, and 28 for microbiological analysis, and fecal scores were subjectively monitored and recorded daily by the same individual. In addition, blood samples were collected from each calf at the end of the trial for immune analysis.ResultsIn comparison to group I, group IV showed a significant increase in both BW and ADG. Specifically, on the 14th and 28th trial days, BW of group IV showed a significant increase of 3.95 and 4.90%, respectively (p < 0.05). Similarly, during the 1–28 trial day period, ADG of group IV showed a significant increase of 28.49% (p < 0.05), whereas their F/G ratio decreased significantly by 22.89% (p < 0.05). No statistically significant difference was observed in BW, ADG, dry matter intake, and F/G ratio (p > 0.05) between groups IV and II. In addition, the fecal score and the diarrhea rate in group IV were significantly reduced by 31.62 and 18.54%, respectively (p < 0.05). No statistically significant difference was observed between groups IV and II (p > 0.05). Moreover, in group IV, IgG and IL-10 levels were significantly increased by 51.97 and 45.45%, respectively (p < 0.05), while IL-1, IL-6, and TNF-α levels were significantly decreased by 30.47, 28.17, and 25.49%, respectively (p < 0.05). Furthermore, a decreasing trend in the number of Escherichia coli and Clostridium perfringens was observed in the fecal microbiota samples obtained from group IV, whereas an increasing trend was observed in the growth of Lactobacillus and Bifidobacterium. Supplementing newborn calves with 500 mg of SBWP per day significantly enhanced the β-diversity indices and demonstrated a trend toward increasing α-diversity in their fecal microbiota, in contrast to the detrimental effects caused by 0.005% gentamicin. Furthermore, 500 mg/day/calf SBWP significantly increased the relative abundance of Lactobacillus and decreased the relative abundance of Escherichia-Shigella. However, no significant difference was observed in the relative abundance of Escherichia-Shigella between the groups receiving 500 mg/day/calf SBWP and 0.005% gentamicin.ConclusionThe findings of this study show that the supplementation of 500 mg/day/calf SBWP to newborn calves significantly improves their growth performance, serum immunity, and intestinal microbiota structure while significantly reducing diarrhea frequency and inflammation. These findings indicate that the supplementation of 500 mg/day/calf SBWP can most effectively enhance the growth performance and reduce the diarrhea frequency in newborn calves.